Competitive Advantage Using Low Cost Higher Education - Makhfudi; Didin Syapeudin; Dwi Andayani (Asia Pacific Journal of Interdisciplinary Studies, 2025)
A university that has a competitive advantage by implementing a Higher Education Competitive Advantage strategy, namely using marketing assets to form a competitive advantage, namely: overall cost advantage or low cost efficiency, differentiation advantage, and focus advantage. This research is categorized as descriptive research which describes the situation and conditions of the internal and external environment of UM Manado in facing competition between universities. qualitative in nature, the dependability test is carried out by auditing the entire research process. The aim of this research is to analyze competitive advantage and formulate competitive advantage strategies using a low cost approach. interviews as a data collection technique. The analytical tool used is value chain analysis which is supported by internal and external environmental analysis tools. Three respondents from UM Manado leadership, Chair of BPH and (Chancellor, Deputy Chancellor for Finance) who represent the condition and character of the data needed in the case study and the Dean and Head of Study Program as confirmatory. The results of this research show that in campus position, Value Chain analysis is used as a cost management analysis tool for making strategic decisions in facing competition. The primary activity that provides the most superior value to UM Manado is the operational and service aspect, while the secondary activity that provides the most value is the quality aspect of human resource management (HRM). Good internal collaboration network (BPH, Rectorate Leadership, PP Muhammadiyah Research and Development Board of Higher Education) Low cost strategy starting from budget planning, use and accountable reporting, providing optimal contribution to competitive advantage.